Computational fluid dynamics based shape optimization of airfoil geometry for an H-rotor using a genetic algorithm. Issue 9 (2nd September 2018) - Daróczy, László; Janiga, Gábor; Thévenin, Dominique
ABSTRACT: Wind energy is continuously growing in importance owing to increasingly strict environmental regulations. Although Horizontal Axis Wind Turbines (HAWTs) are the most popular, Vertical Axis Wind Turbines, especially H-Darrieus turbines, are gaining interest owing to their numerous advantages and lower cost. To remain competitive, the industry is increasingly considering the optimization of wind turbines. The present work therefore considers the optimization of an H-Darrieus wind turbine using a genetic algorithm, owing to its robustness; the airfoil shape is varied to maximize the energy output at the optimal tip-speed ratio using detailed unsteady, turbulent, computational fluid dynamics simulations relying on the commercial tool StarCCM+. Following a description of the analysed rotor, automation and validation, the optimization is carried out with the k – ω SST turbulence model. Nearly 900 configurations are evaluated. Thanks to the analysis, a configuration is identified that provides considerably improved performance for all tip-speed ratios.